Malnutrition and Right to Health: An Interface - D, Rangaswamy (Kathmandu School of Law Review, 2024)
The Right to Health (RTH) is one of the most asserted and consistently talked about rights under human rights jurisprudence. Because of the myriad issues surrounding it, it is one of the most frequently violated rights in recent times. RTH is the bundle of diverse rights. Right to Food (RTF) is one of the intrinsic components of RTH. The RTF can be realized when every man, woman and child, alone or in community with others, has physical and economic access at all times to adequate food or means for its procurement. Right to Nutritious Food (RNF) is an innate part of RTF. RTH, RTF and RNF are closely integrated and intertwined. Hunger and malnutrition are chronic, structural problems that are worsening in the wake of the crises in food prices, finance and the climate. Despite hundreds of millions of dollars poured annually into development assistance, including food aid and agricultural development, over the past 60 years, the numbers of people who are poor, hungry and under-nourished have continued to grow. In this background, this paper reviews the existing challenges and issues connected with RTH, RTF and RNF in the background of malnutrition. The paper concludes that unless the existing laws are implemented in their letter and spirit, it would be difficult for the system to overcome these challenges. The paper also asserts that there is a need for compliance of moral standards by each and every stakeholder being responsible for implementation of these rights.